2013
DOI: 10.4236/ojic.2013.33009
|View full text |Cite
|
Sign up to set email alerts
|

Visible photoluminescence of polyoxoniobates in aqueous solution and their high electrocatalytic activities for water oxidation

Abstract: ABSTRACT14− was observed, and its origin was revealed in the view of molecular orbital by means of the computational method. The photoluminescence is originated from singlet transitions, and the calculated values agree well with the experimental data. The results indicate that the size of clusters and the foreigner atoms can affect the fluorescent properties of PONbs. The absorption and emission of these PONbs are originated molecular orbitals contributed mainly by μ 2 -O and Nb atoms according to NBO analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…It was found that the calculated values are in a good agreement with the experimental data. The obtained results proved also the impact of clusters size and addenda atoms on the catalytic and fluorescent properties of PONbs (Ye et al, 2013 ).…”
Section: Catalysis On Polyoxoniobatessupporting
confidence: 61%
“…It was found that the calculated values are in a good agreement with the experimental data. The obtained results proved also the impact of clusters size and addenda atoms on the catalytic and fluorescent properties of PONbs (Ye et al, 2013 ).…”
Section: Catalysis On Polyoxoniobatessupporting
confidence: 61%
“…Paramagnetic Cu­(II) ions are renowned for their quenching effect on intraligand π L * → π L transitions and the resulting fluorescence of surrounding fluorophores through electron and energy transfers. , However, in Cu­(II) complexes with phen ligands with 5-fold coordination geometry intermediate between trigonal bipyramidal and square pyramidal, an emission could be observed. , Compound I was excited with UV light (λ ex = 275 nm), leading to a luminescence spectrum (Figure S11) with broad emission signals at 386 and 408 nm. These signals are slightly shifted to higher values in comparison to literature data but could be assigned to the phen ligand as π L * → π L transitions. ,, The shoulder at 461 nm might be caused by the hexaniobate unit, which contributes with HOMO to LUMO transitions showing broad signals at around 400 nm upon irradiation with λ ex = 294 nm . A shift to higher wavelength is in some cases observed when polyoxoniobates are connected to Cu­(II) complexes with phen ligands. , The emission signal at 650 nm corresponds to red light, which could be observed as a faint glow during the measurement.…”
Section: Resultsmentioning
confidence: 69%
“…35,87,90 The shoulder at 461 nm might be caused by the hexaniobate unit, which contributes with HOMO to LUMO transitions showing broad signals at around 400 nm upon irradiation with λ ex = 294 nm. 97 A shift to higher wavelength is in some cases observed when polyoxoniobates are connected to Cu(II) complexes with phen ligands. 46,47 The emission signal at 650 nm corresponds to red light, which could be observed as a faint glow during the measurement.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Then, we applied (TMA) 6 [Nb 10 O 28 ]$6H 2 O as homogeneous catalyst for aldol-type condensation reactions such as Knoevenagel and Claisen-Schmidt condensation reactions and revealed for the rst time that it acted as a Brønsted base catalyst whose strength is comparable to superbases. This result will open up a new possibility of application of PONbs since their catalytic application has been limited to electrocatalysts 13 and photocatalysts so far. [14][15][16][17]…”
Section: Introductionmentioning
confidence: 99%